Investment Casting of AZ91 Magnesium Open-Cell Foams - H. Kapłon; A. Dmitruk; K. Naplocha (Archives of Foundry Engineering, 2023)
The process of investment casting of AZ91 magnesium alloy open-cell porosity foams was analysed. A basic investment casting technique was modified to enable the manufacturing of magnesium foams of chosen porosities in a safe and effective way. Various casting parameters (mould temperature, metal pouring temperature, pressure during metal pouring and solidifying) were calculated and analysed to assure complete mould filling and to minimize surface reactions with mould material. The foams manufactured with this method have been tested for their mechanical strength and collapsing behaviour. The AZ91 foams acquired in this research turned out to have very high open porosity level (>80%) and performed with Young’s modulus of ~30 MPa on average. Their collapsing mechanism has turned out to be mostly brittle. Magnesium alloy foams of such morphology may find their application in fields requiring lightweight materials of high strength to density ratio or of high energy absorption properties, as well as in biomedical implants due to magnesium’s high biocompatibility and its mechanical properties similar to bone tissue.